Effect of palm oil fuel ash (POFA) toward foam concrete compressive strength and microstructure - Nur Fadilah Hanim, Mohd Nasir (2014)
Malaysia is well known as the main crude palm oil producer and exporter in the world. Million tons of agro wastes such as palm oil fuel ash (POFA) is being produced every year with no commercial return on it. Due to the pozzolanic behavior possessed by POFA, it could be significance when the POFA is being recycled and used in production of lightweight foamed concrete (LWFC). Thus, the aim of this research is to study the effects of POFA on engineering properties and microstructure of LFC with 1 600kg/m3 until 1800kg/rn 3 of density in terms of compressive strength, porosity, scanning electron microscope (SEM) and thermal gravimetric analysis (TGA). Four types of foamed concrete were prepared with different percentage LWC with 0%, 10%, 20% and 30%. All the specimens were water cured before being tested. At the 20% concrete containing of POFA had a highest strength which is 11.2, 15.15 and 29.20 MPa and lower porosity is 14.99, 11.94 and 9.54. It is proved that the percentage of porosity is lest and the strength of the other specimen is higher. Besides, it was found that the micro structure of LFC was denser and the pore size of the structure was refined with the presences of POFA, compared with that of control mix. Effective consumption of POFA as a pozzolanic material in concrete can decrease the cost of concrete production, save environmental and also can solve the landfill problem